STUDENTS’ ENGLISH LANGUAGE CHALLENGES AND IMPROVEMENT STRATEGIES AT POLITEKNIK ELBAJO COMMODUS, LABUAN BAJO: A DESCRIPTIVE SURVEY STUDY - Natalia Dellarosa Halim; Dominikus Seno; Maria Beatrix Rahinart Wellalangi; Layliyatul Faiqiyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
English proficiency is an essential competency for vocational higher education students, particularly in tourism destinations; however, studies simultaneously examining students' English language challenges and improvement strategies within vocational contexts remain limited. This study aims to identify the major challenges encountered by students in using English and analyze the strategies they expect to improve their English proficiency. A descriptive survey employing a mixed-methods approach was conducted with 86 students from eight study programs at Politeknik eLBajo Commodus. Data were collected through open-ended questionnaires and analyzed using thematic analysis supported by descriptive statistics. The findings reveal that the primary challenges include lack of confidence and fear of making mistakes (68%), limited vocabulary (63%), weak grammar skills (41%), lack of a supportive English-speaking environment (37%), and pronunciation and listening difficulties (26%). Students recommended increasing speaking practice, implementing consistent English use on campus, establishing conversation clubs, and strengthening lecturers' encouragement during classroom interaction. This study offers a comprehensive mapping of psychological, linguistic, and environmental barriers alongside students' proposed improvement strategies, providing evidence for developing communicative learning practices and institutional policies to enhance English proficiency in vocational higher education. ABSTRAK Kemampuan berbahasa Inggris merupakan kompetensi penting bagi mahasiswa pendidikan tinggi vokasi, khususnya di kawasan pariwisata, namun penelitian yang mengkaji secara bersamaan tantangan penggunaan bahasa Inggris dan strategi peningkatannya berdasarkan persepsi mahasiswa pada konteks vokasi masih terbatas. Penelitian ini bertujuan mengidentifikasi tantangan utama penggunaan bahasa Inggris serta menganalisis strategi yang diharapkan mahasiswa untuk meningkatkan kemampuan berbahasa Inggris. Penelitian menggunakan desain survei deskriptif dengan pendekatan mixed methods. Data dikumpulkan melalui kuesioner terbuka yang diberikan kepada 86 mahasiswa dari delapan program studi di Politeknik eLBajo Commodus dan dianalisis menggunakan analisis tematik yang didukung statistik deskriptif. Hasil penelitian menunjukkan bahwa tantangan utama meliputi kurangnya rasa percaya diri dan takut melakukan kesalahan (68%), keterbatasan kosakata (63%), kelemahan tata bahasa (41%), kurangnya lingkungan berbahasa Inggris (37%), serta kesulitan pelafalan dan menyimak (26%). Mahasiswa mengusulkan peningkatan praktik berbicara, penerapan penggunaan bahasa Inggris secara konsisten di kampus, pembentukan klub percakapan, dan penguatan peran dosen. Penelitian ini menawarkan pemetaan terpadu mengenai hambatan psikologis, linguistik, dan lingkungan beserta strategi perbaikannya sebagai dasar pengembangan pembelajaran komunikatif dan kebijakan institusi untuk meningkatkan kompetensi berbahasa Inggris mahasiswa vokasi.